The Exchange Rates and Stock Return: The Case of Tourism Sub Sector in Indonesia - Hernowo, Andre; Pratama, Yudha Sakti (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the effect of exchange rates on stock prices, by taking a sample of the tourism sub-sector companies listed on the Indonesia Stock Exchange 2015-2019 period. The sampling technique used in this study using judgment sampling as many as 22 companies engaged in the sector. The data collection method uses secondary data processing obtained from the official website of the institution that is relevant to this research. This study uses a quantitative approach using linear regression analysis, to know the direction and how much influence the independent variable has on the dependent variable. From the results of data processing, it is known that the exchange rate has a positive and significant effect on stock prices